Green Consumers, Emission Taxes, and Firm Relocation - Laura Birg; Jan Voßwinkel (ZBW - Leibniz Information Centre for Economics, 2020)
This paper studies the interaction of environmental policy and green preferences under potential firm relocation. A green firm and a brown firm choose the environ- mental quality of their products. Both an emission tax and consumers'willingness to pay for green products encourage investment in environmental quality. Firms may relocate to avoid taxation or abstain from investment in environmental quality to produce at lower cost. If the green firm does not relocate, both the green firm and the brown firm provide higher quality levels. Compared to first-best taxation, the equilibrium emission tax is lower (higher) if only the brown (green) firm relocates.
Keywords: H23; F18; L13; Q58; 330; environmental policy; emission tax; green consumers; relocation